A vocação fantasma dos navios: Subjetividade e espaço urbano no romance de Ronaldo Costa Fernandes. Issue 4 (1st October 2016) - Lima, Rogério
ABSTRACT: This article analyzes the novel Um homem é muito pouco by Ronaldo Costa Fernandes in order to examine the representation of subjectivity of the four characters who narrate different sections of the novel; the importance of the description of the urban spaces in the narrative; and the integration of literary reference as a form of narrative development. The article also highlights memory as a most important element in the narrative—specifically, the recollections by the four narrators-characters of situations experienced during the 1964–1985 Brazilian civic-military dictatorship.